First Experiences with Online Last Aid Courses for Public Palliative Care Education during the COVID-19 Pandemic - Bollig, Georg (Healthcare (Basel), 2021)
The Last Aid course aims to teach public palliative care by increasing public awareness and empowering people about the role of the individual in the death of loved ones. The Covid-19 pandemic, however, has altered educational methods prohibiting classroom settings. Therefore, an online course was created to enable continued and safe public palliative care education. A mixed-methods study was performed to examine the feasibility of delivering the Last Aid course online. Data collection included participant questionnaires with qualitative and quantitative data, observations and a focus group discussion. Data were analyzed using descriptive analysis and qualitative description. In total, 15 online Last Aid courses were held, 174 participants took part in the study and 92 completed questionnaires were included. Findings revealed overall course satisfaction for the online courses in line with previous findings for classroom teaching. The online platform enabled course participation from people previously unable or unwilling to attend, namely caregivers to dying relatives and younger people. Instructors displayed an ability to teach online. However, some instructors expressed frustration over reduced interaction and technical challenges, which was echoed by participant ratings showing that many lacked social networking with fellow participants. Nonetheless, this pilot study demonstrates the feasibility of the online Last Aid course. Attention must be given to increasing both participant-to-participant and instructor-to-participant interaction. More research on the long-term effects of Last Aid courses is needed.